Status and developments of CRDF grant applications with the MTDC - UMP, PNC (Penerbit UMP, 2009)
A meeting to discuss the status of Commercialisation RDF grants took place on 24 Feb 2009 at the Malaysia Technology Development Corporation (MTDC), Menara Tun Razak.